2005
DOI: 10.1051/forest:2005046
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the photosynthetic capacity across a chronosequence of maritime pine correlates with needle phosphorus concentration

Abstract: -Changes in needle photosynthetic capacity has been studied across a chronosequence of four maritime pine stands aged 10-, 32-, 54-and 91-yr. We determined photosynthetic parameters from response curves of assimilation rate to air CO 2 concentration (A-C i ) and radiation (A-Q) using gas exchange measurements on branches in the laboratory. Our data showed no shift in photosynthetic parameters (V cmax , J max , α and R d ) with increasing stand age. This result means that the decline in productivity observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…In maritime pine, Ben Brahim et al [2] have reported that under moderate P deficiency (between 0.0013 and 0.0017 g P per g dry matter in plants), the lower plant growth was paralleled by a slower development of the foliage. Under more severe P deficiencies (between 0.0004 and 0.0013 g P per g dry biomass) a tight negative correlation was observed between phosphorus leaf concentration and photosynthetic capacity [15,34]. Our experiment was conducted in the intermediate range of P deficiencies, so that the absence of effect of P treatments on RUE is consistent with these results.…”
Section: Discussionsupporting
confidence: 75%
“…In maritime pine, Ben Brahim et al [2] have reported that under moderate P deficiency (between 0.0013 and 0.0017 g P per g dry matter in plants), the lower plant growth was paralleled by a slower development of the foliage. Under more severe P deficiencies (between 0.0004 and 0.0013 g P per g dry biomass) a tight negative correlation was observed between phosphorus leaf concentration and photosynthetic capacity [15,34]. Our experiment was conducted in the intermediate range of P deficiencies, so that the absence of effect of P treatments on RUE is consistent with these results.…”
Section: Discussionsupporting
confidence: 75%
“…Altitudinal increase in leaf nitrogen content has already been observed for other species (Cordell et al, 1998;Premoli and Brewer, 2007). Photosynthetic capacity tends to be positively related to higher values of foliar nitrogen and phosphorus due to increased levels of Rubisco and other N-containing constituents of the photosynthetic apparatus (Delzon et al, 2005;Field and Mooney, 1986;Marron et al, 2008). Moreover, only for beech, our results also suggest that at least part of the increase in maximum assimilation rate at high elevation may be attributed to a slight increase in stomatal conductance, implying an increase in CO 2 diffusion into the leaf.…”
Section: Discussionmentioning
confidence: 84%
“…The age-dependent photosynthetic decrease has been attributed to the stronger difficulties for water flux that occur with increases in tree height and architectural complexity along with age, which promote lower stomatal conductance for CO 2 diffusion into intercellular spaces (Ryan and Yoder 1997;Bond 2000). Photosynthesis of older trees, however, has been observed to decrease even at relatively high intercellular CO 2 concentrations (Day et al 2001;Niinemets 2002; but see Delzon et al 2005), indicating that the biochemical potential for photosynthesis (i.e., non-stomatal limitations) may be constrained with age. Other studies suggest that photosynthetic decay on older trees may be part of a genetically controlled maturation process (Becker et al 2000;Bond 2000;Day et al 2001).…”
Section: Introductionmentioning
confidence: 96%